2022
DOI: 10.3390/children9111632
|View full text |Cite
|
Sign up to set email alerts
|

Sialendoscopy in Management of Juvenile Recurrent Parotitis—A Single Centre Experience

Abstract: Juvenile recurrent parotitis is a rare inflammatory disease of the parotid gland that shares diverse therapeutic management between institutions. Sialendoscopy has been demonstrated as an efficient diagnostics and therapeutic method with minimal complications; however, due to the rarity of the disease and limited data, there is a lack of universal guidelines on its optimal management. Herein, we retrospectively analysed patients with juvenile recurrent parotitis who had the sialendoscopy performed at our terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…It should be noted that the need for repeated sialoendoscopy treatments to completely resolve symptoms is commonly described in the literature [1,20,[49][50][51][52], even up to five times. It is reported that the recurrence of swellings after treatment, if it does occur, tends to be less intense and less painful and the treatment can be performed again in cases of several recurrences of swellings [8,24,27]. In this study, two children (12%) needed a second intervention, and one child (6%) needed up to four interventions in order to reach a successful treatment result.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…It should be noted that the need for repeated sialoendoscopy treatments to completely resolve symptoms is commonly described in the literature [1,20,[49][50][51][52], even up to five times. It is reported that the recurrence of swellings after treatment, if it does occur, tends to be less intense and less painful and the treatment can be performed again in cases of several recurrences of swellings [8,24,27]. In this study, two children (12%) needed a second intervention, and one child (6%) needed up to four interventions in order to reach a successful treatment result.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, another study showed that 90% of participants were free of symptoms after only one endoscopy procedure [46]. A recent study [27] described 76% of patients as symptom-free, but only for the first year after the procedure. A meta-analysis that included seven studies showed a success rate with no further sialoendoscopy needed at 87% [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations